Evaluation of the International Special Class Program at UIN Sultan Aji Muhammad Idris Samarinda CIPP Model Study - Galby Silvia; Imroh Atul Musfiroh; Zurqoni Zurqoni; Heri Retnawati (Fakultas Tarbiyah dan Ilmu Keguruan UIN Sultan Aji Muhammad Idris Samarinda, 2026)
The International Special Class (KKI) Program at UIN Sultan Aji Muhammad Idris Samarinda strategically responds to the demands of PTKIN internationalisation. Since 2017, a comprehensive program evaluation has not been conducted. The purpose of this study is to evaluate the effectiveness of the KKI program using the CIPP model. Qualitative methods with semi-structured interviews, observation, and document analysis. The research subjects included: managers, lecturers, and KKI students. The results of this study from the context dimension are quite strong, but still weak in the legitimacy of special policies. The input dimension is still weak, student selection is good, but bilingual lecturer human resources and budget are limited. The Process dimension is still lacking due to the decentralisation of methods without bilingual pedagogical standards. From the Product dimension aspect, it is good, marked by student achievements across generations that have been documented but not systematically. Reflection of the aspiration-implementation gap experienced by PTKIN in developing international standard programs.